Analysis of Teachers' Pedagogic and Professional Competence in Utilizing TPACK - Wafa, Muhammad Amiruddin; Sutomo, Imam (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to analyze the pedagogical and professional competencies of teachers in utilizing TPACK in science learning, as well as the supporting and inhibiting factors of teacher pedagogical and professional competencies in utilizing TPACK which were carried out at MIN Krandon and MI Wonorejo, Guntur District, Demak Regency. This type of research uses descriptive qualitative research. The subjects of this study were class V teachers. The data were obtained through interviews, observation and documentation. Data analysis techniques through data reduction, data presentation and drawing conclusions. The results of the study show that teachers carry out pedagogic competencies in science learning, teachers can understand the different characters of students well, teachers can develop learning materials and educational learning activities, teachers are able to develop teaching materials through digital technology, and create learning media IT-based, teachers can use the internet for media needs for their duties as educators and utilize TPACK, in professional competence, teachers deliver structured material, determine strategies and learning models that are tailored to students, in utilizing TPACK teachers are able to operate technology in preparing learning designs, teachers are able to access the internet to convey science material that is used as a learning media in class.